Perancangan Sistem Informasi Rekam Medis Berbasis Web Pada Unit Kesehatan Sekolah IDN Boarding School Jonggol - Mulyana, Dadang Iskandar; Ramadhan, Gilang; Ardana, Tegar Rizky; Aimar, Muqorrobin; Saputra, Mochammed Erryandra (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
In this modern era, many Islamic boarding schools have built their own Health Units. However, often these units only function as an effort to prevent and overcome student health problems in general. The more students there are in an Islamic boarding school, the more important it is for the Health Unit in the Islamic boarding school to innovate to improve the quality of its services. The concept of designing this information system refers to the activity of processing student medical record data that occurs in the Health Unit which is still manual, so a website-based medical record information system is needed at the IDN Jonggol Islamic boarding school which is computerized to solve this problem. This research aims to produce a software application that is expected to help the Health Unit in processing student data collection which can make it easier to search and make reports. To support this research, data collection methods are carried out using observation, interviewing, literature study, analysis, and design system, building the system, testing, and implementing the system. The implementation of the medical record information system at the IDN Jonggol Islamic boarding school has succeeded in increasing the efficiency, accuracy, and accessibility of student health data, providing convenience in making reports, and supporting improvements in the quality of health services